Prevalence of molar incisor hypomineralization in India: A systematic review and meta-analysis - Ashveeta J Shetty; Uma B Dixit; Richard Kirubakaran (Wolters Kluwer Medknow Publications, 2022)
Research Question: To estimate the pooled prevalence of molar incisor hypomineralization (MIH) in children from India. Research Protocol: The PRISMA guidelines were followed. Literature Search: An electronic search of the databases was performed to find prevalence studies of MIH in children above age 6 years in India. Data Extraction: Two authors independently extracted the data from the 16 included studies. Quality Appraisal: The risk of bias was assessed using a modified version of the Newcastle-Ottawa Scale adapted for cross-sectional studies. Data Analysis: The pooled prevalence estimate of MIH was calculated using logit transformed data with inverse variance approach in a random-effects model with 95% confidence interval (CI). Heterogeneity was assessed with the I2 statistic. The subgroups were analyzed to assess the pooled prevalence of MIH according to sex, arch-wise proportion of MIH-affected teeth, and proportion of children with the MIH phenotypes. Results and Interpretation of Results: Sixteen studies included in the meta-analysis represented 7 states of India. A total of 25,273 children were included in the meta-analysis. The pooled prevalence of MIH in India was estimated to be 10.0% (95% CI: 0.07, 0.12) with significantly high heterogeneity between the included studies. The pooled prevalence did not vary according to sex. The pooled proportions of MIH-affected teeth were similar in the maxillary and mandibular arches. The pooled proportion of children with MH phenotype was higher (56%) than those with M + IH phenotype (44%). Further studies with standardized criteria for recording MIH are needed to ascertain the prevalence of MIH in India.